The twelve months' follow‐up, second version, after an intervention using a rehabilitation program of physical and cognitive rec‐xercise (REPCREC) for the elderly with mild cognitive impairment (MCI): Dementia care research (research projects; nonpharmacological)/Therapeutic strategies and interventions. (7th December 2020) - Kanemaru, Akiko; Kato, Takayuki; Honda, Takuya; Hiraoka, Tomo; Kawaji, Yoshie; Makita, Ayaka; Kuwata, Naoya; Shimizu, Aya; Higuchi, Wakana; Sugawara, Yasuhiro; Uemura, Honoka; Yamazaki, Ritsuko; et al.
Abstract: Background: Whether our rehabilitation program of physical and cognitive Rec‐Xercise (REPCREC) for the elderly with MCI can bring any difference in cognition and QOL. Method: Subjects are sixty‐nine cases, out of 73 enrolled individuals for more than three years, have undergone our evaluation and intervention program (REPCREC). The subjects have been divided into four groups; group A has taken the cognitive REPCREC, group B physical REPCREC, group C both cognitive and physical REPCREC and group D control. The design of this study is a non‐randomized controlled trial. Three intervention groups have received the each session once per week up to 12 times. Before and after the intervention, and, three, six and twelve months after the intervention, we have evaluated the following items: physical function, Geriatric Depression Scale, POMS2, Visual analog scale (VAS‐1: healthy life, VAS‐2: satisfaction), neuropsychological tests [MMSE, RBMT, TMT, Ravenʼs Colored Progressive Matrices (RCPM), Rey‐Osterrieth Complex Figure Test (ROCF), story retention, coding and Miyake's paired verbal associate learning test (MPVALT)]. A one‐day booster program has been provided at the time of evaluation. For statistical analysis, Fisher's exact test and Kruscal‐Wallis test for the baseline data, and linear mixed model (LMM) analysis and Friedman's test for the prolonged effect of REPCREC have been performed. Results: The median age 79.0 years old, median MMSE score 28.0 points, the number of each group is A 22, B 22, C 25, and D 7cases. At the baseline, no difference between groups. LMM analysis revealed the significant difference in RCPM, ROCF (recall), MPVALT (non‐related), MPVALT (related), coding and VAS‐2 (respectively p=0.000, 0.000, 0.000, 0.001, 0.011 and 0.006). Friedman's test showed significant difference in RCPM of group A (p=0.046) and C (p=0.042), ROCF (recall) group C (p=0.022), VAS‐2 of group A (p=0.013) and C (p=0.011), MPVALT (non‐related) of group A (p=0.007), MPVALT (related) of group A (p=0.016) and C (p=0.048). Conclusions: The program REPCREC showed the prolonged effects on non‐verbal intelligence, visuospatial abilities, memory, attention, planning, working memory etc. [(RCPM), ROCF (recall), MPVALT] in group A and C comparing with control in the elderly with MCI.